2020
DOI: 10.1155/2020/1027271
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Synergistic Mechanisms of Multiple Ingredients in Shuangbai Tablets against Proteinuria by Virtual Screening and a Network Pharmacology Approach

Abstract: Shuangbai Tablets (SBT), a traditional herbal mixture, has shown substantial clinical efficacy. However, a systematic mechanism of its active ingredients and pharmacological mechanisms of action against proteinuria continues being lacking. A network pharmacology approach was effectual in discovering the relationship of multiple ingredients and targets of the herbal mixture. This study aimed to identify key targets, major active ingredients, and pathways of SBT against proteinuria by network pharmacology approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 107 publications
(102 reference statements)
0
4
0
Order By: Relevance
“…Virtual screening and network pharmacology are effective ways to find the relationship between multiple components and targets of TCM [64,65]. In the present study, we identified the systemic mechanisms of GXV in the treatment of CAD by these approaches, which provides a new strategy to study the potential active components and targets of TCM [66,67].…”
Section: Discussionmentioning
confidence: 92%
“…Virtual screening and network pharmacology are effective ways to find the relationship between multiple components and targets of TCM [64,65]. In the present study, we identified the systemic mechanisms of GXV in the treatment of CAD by these approaches, which provides a new strategy to study the potential active components and targets of TCM [66,67].…”
Section: Discussionmentioning
confidence: 92%
“…KEGG consists of artificially annotated metabolic pathways and defines the complex interrelationship between genes and metabolites [ 33 ]. R project software has been widely used in network pharmacology studies for screening of DEGs, enrichment, and annotation analysis [ 37 , 44 ].…”
Section: Methodsmentioning
confidence: 99%
“…Through network pharmacology, data on ingredients, diseases, and their related targets are often gathered through existing online databases, and visualization software is then used to systematically analyze TCMs by constructing an "ingredienttarget-pathway" network, so as to define the drug intervention and the treatment effects on different diseases (9). The systematic nature of network pharmacology is consistent with the holistic view and syndrome differentiation theory of TCM has been widely applied to the study of TCM to generate new research data, methods and results (10)(11)(12). Based on this approach, we used network databases to construct an "ingredient-target" network, a PPI network for enrichment analysis.…”
Section: Introductionmentioning
confidence: 99%